TDRR Model Equations with Bulk Reaction Between the Burn Surfaces - Partom, Yehuda (European Journal of Applied Sciences, 2022)
The reaction rate of our reactive flow model (TDRR) is determined by the moving burn fronts emanating from hot spots and any bulk reaction between those fronts is ignored. Our TDRR reaction rate depends on the reactant temperature, and has a multiplier called Burn Topology Function (BTF), that from lack of specific knowledge we’re not changing for different situations. Recent shock initiation tests with the explosive PBX9502 show that our TDRR reaction rate is somewhat too slow towards the end of the reaction. To account for this small discrepancy, we check the assumption that what increases the reaction rate in a computational cell is the bulk reaction between the reaction fronts towards the end of the reaction. This calls for expanding TDRR to include this bulk reaction. We find that including the bulk reaction has very little influence on the end result. We then check whether by changing somewhat our BTF can move our computational results closer to the test results. We find that by increasing somewhat the initial value of our BTF, we’re able to adjust our reactant burn rate to get a better agreement with test results.